2017
DOI: 10.15171/jcs.2017.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nursing Care Based on Watson’s Theory of Human Caring on Anxiety, Distress, And Coping, When Infertility Treatment Fails: A Randomized Controlled Trial

Abstract: Introduction: The failure of infertility treatment leads to individual, familial, and social problems. The objective of this study was to evaluate the effectiveness of the nursing care program based on Watson’s "Theory of Human Caring" on anxiety and distress caused by coping when the treatment fails. Methods: This study randomized controlled trial study was conducted from April to November 2012, with 86 Turkish women with infertility (intervention group: 45, control group: 41). Follow-up of 32 infertile women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 38 publications
1
13
1
5
Order By: Relevance
“…Healthy coping strategies on the other hand, have been shown to help women weather the difficulties of infertility with better mental health outcomes. 26,44,45 Unlike previous studies that have found that higher education was a protective factor for infertility and related mental health distress, 3,14 educational level was not significant in the current study. This may be due to the fairly even low educational levels of our slum-dwelling participants, ranging mostly (>70%) from illiteracy, to highersecondary.…”
contrasting
confidence: 97%
“…Healthy coping strategies on the other hand, have been shown to help women weather the difficulties of infertility with better mental health outcomes. 26,44,45 Unlike previous studies that have found that higher education was a protective factor for infertility and related mental health distress, 3,14 educational level was not significant in the current study. This may be due to the fairly even low educational levels of our slum-dwelling participants, ranging mostly (>70%) from illiteracy, to highersecondary.…”
contrasting
confidence: 97%
“…Infertility diagnosis and the subsequent treatment process usually impose excruciating stress on couples. Several studies have reported that couples with infertility are prone to experiencing depression (6), anxiety (7), sexual intercourse problems, marital problem (8,9), decrease in selfconfidence (10), and low levels of psychological well-being (11,12) and quality of life (13).…”
Section: Introductionmentioning
confidence: 99%
“…Non-caring models are more task-oriented than psychological and social aspects; these models can lead to patient dissatisfaction as a main threat to quality care [7]. Watson’s theory was used in different fields of nursing [8,9]. This suggests that it is necessary to address and assess nurses’ caring experience to improve their awareness, as well as their caring outcomes [10].…”
Section: Introductionmentioning
confidence: 99%